2021
DOI: 10.34133/2021/8175709
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying Electron Utilization by Surface-Anchored Rh Complex for Enhanced Nicotinamide Cofactor Regeneration and Photoenzymatic CO 2 Reduction

Abstract: Solar-driven photocatalytic regeneration of cofactors, including reduced nicotinamide adenine dinucleotide (NADH), reduced nicotinamide adenine dinucleotide phosphate (NADPH), and reduced flavin adenine dinucleotide (FADH2), could ensure the sustainable energy supply of enzymatic reactions catalyzed by oxidoreductases for the efficient synthesis of chemicals. However, the elevation of cofactor regeneration efficiency is severely hindered by the inefficient utilization of electrons transferred on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Generally, an EPCS comprises numerous elemental components, such as enzyme, photocatalyst, cofactor, reactant, and product, which can be categorized into three modules: cofactor regeneration module, cofactor utilization module, and cofactor shuttling module. These three modules jointly govern the overall efficiency of an EPCS. , In recent years, cofactor regeneration module and cofactor utilization module have been extensively explored through rational designing/screening of the photocatalyst and enzyme to enhance the reation rates. In contrast, cofactor shuttling module, which is responsible for the mass and energy exchange between cofactor regeneration module and cofactor utilization module, has been much less concerned until now. The core of cofactor shuttling module is to delicately match the slower mass transfer (occurring at the time scale of ns to ms) , and the faster reaction (occurring at the time scale of ps to ns), which highlights the coordinative optimization within a very small time-scale and should be rationally addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, an EPCS comprises numerous elemental components, such as enzyme, photocatalyst, cofactor, reactant, and product, which can be categorized into three modules: cofactor regeneration module, cofactor utilization module, and cofactor shuttling module. These three modules jointly govern the overall efficiency of an EPCS. , In recent years, cofactor regeneration module and cofactor utilization module have been extensively explored through rational designing/screening of the photocatalyst and enzyme to enhance the reation rates. In contrast, cofactor shuttling module, which is responsible for the mass and energy exchange between cofactor regeneration module and cofactor utilization module, has been much less concerned until now. The core of cofactor shuttling module is to delicately match the slower mass transfer (occurring at the time scale of ns to ms) , and the faster reaction (occurring at the time scale of ps to ns), which highlights the coordinative optimization within a very small time-scale and should be rationally addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, NAD + has been reduced to NADH through biocatalysis with sacrificial reagents, such as formic acid, 15–18 and photo(electro)catalysis with noble metal complexes such as [Cp*Rh(bpy)(H 2 O)]Cl 2 , 19–25 which is coupled with enzyme-catalyzed reduction reactions. 19,24,26–31 However, there are product separation difficulties and serious problems of mutual inactivation of molecular and enzymatic catalysts due to their interaction. 32–34 Heterogeneous NAD + hydrogenation to NADH with H 2 as the reducing agent can avoid the above issues, but the selectivity for 1,4-NADH is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the steady-state PL intensity of photocatalysts decreased after modification of M . This is because the anchored M can capture more photoexcited electrons and utilize them quickly, thereby suppressing the recombination of photoexcited electron–hole pairs . In addition, with the decrease of the thickness of the Rh-COF Bpy shell, both the PL spectra first decreased and then increased, and Rh-COF Bpy @HCOF 25 showed the lowest PL intensity (Figure S14), which showed that Rh-COF Bpy @HCOF 25 had the highest photogenerated electron–hole separation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The electron lifetime of Rh-COF Bpy @HCOF is shorter than that of COF Bpy @HCOF, because the M could accept and store electrons in the form of hydrides (Rh−H) and then improve the efficiency of electron utilization. 33,36 We then calculated their electron utilization efficiencies (EUE) by testing the open-circuit potential (OCP) of COF Bpy @HCOF 25 and Rh-COF Bpy @HCOF 25 with the equation: 36,47 i k j j j j j y…”
Section: ■ Results and Discussionmentioning
confidence: 99%